Integrated and collaborative process-based simulation framework for construction project planning. (2017) - Ismail, Ali; Srewil, Yaseen; Scherer, Raimar J.
This paper presents an integrated process-based construction simulation toolkit (CST) and a web-based collaboration platform named ProSIM to support planning of construction projects using simulation technique. The data integration between the simulation model and the project information is based on building information modelling (BIM) and multi-model data exchange approaches. CST aims to support planning and optimisation of production and logistic operations of construction projects. It targets rapid development of simulation models and efficient integration of simulation input data from various data models and capturing realtime data. ProSIM is a web-based portal enabling the collaboration among the simulation experts and project planning teams. The paper gives an overview about the simulation framework architects and focuses on the integration of simulation input data for four basic project data models, namely: product model based on IFC standards, process models and simulation templates based on BPMN notation, planning and resources data and real-time data fusion technology. It discusses and presents the latest research work and the prototype implementation through case studies.